Augmented versus non-augmented percutaneous cementoplasty for the treatment of metastatic impending fractures of proximal femur: A systematic review. (August 2020) - Kitridis, Dimitrios; Saccomanno, Maristella Francesca; Maccauro, Giulio; Givissis, Panagiotis; Chalidis, Byron
Abstract : Percutaneous cementoplasty has been used for the stabilization of impending fractures of the proximal femur due to metastatic lesions. Augmentation with fixation devices aims to improve mechanical consolidation and stability. Both techniques appeared effective in terms of resolution of symptoms, prevention of fractures, and early facilitation of weight-bearing. Augmented cementoplasty does not seem to improve outcomes when compared with cementoplasty alone. Cementoplasty alone showed more clinical safety compared with augmented cementoplasty. Abstract: Introduction: Percutaneous cementoplasty (PC) has been widely used for the stabilization of impending fractures of the proximal femur due to metastatic lesions. Augmented percataneous cementoplasty (APC) with fixation devices aims to improve mechanical consolidation and stability of the construct. However, the clinical benefit of the combined technique has not been clearly established. The purpose of the current review was to compare the efficacy between APC and PC for impending pathologic proximal femoral fractures from metastatic malignancy, in terms of pain relief, operative time and fracture related complication rates. Material and methods: Medline, Scopus, and the Cochrane central register of controlled trials were searched for clinical studies up to July 2019. Studies relevant to cementoplasty of the proximal femur were included. The primary outcome of the study was pain relief as assessed using the Visual Analogue Scale (VAS) change. Secondary outcomes included incidence of post-intervention fracture, operative time and complication rate. Results: Twelve studies with a total of 343 patients were included. No difference was found for all outcomes. For pain relief, pooled results showed a mean difference in VAS score -4.6 ± 1.7 for PC, and -4.3 ± 2.5 for APC ( p = 0.41). Post-intervention fractures of the proximal femur occurred in 7% of patients with PC and in 5% of patients with APC ( p = 0.4), and the mean duration of interventions was 57.9 ± 8.4 and 56.5 ± 27.5 min, respectively ( p = 0.58). Cement leakage into the hip joint or the soft tissues occurred in 5% of cases in PC group and in 8% of cases in APC group ( p = 0.16). Six patients in the APC group (4%) experienced major systemic complications, which were treated successfully. Conclusions: APC does not seem to improve pain relief, fracture incidence, and operative time when compared with PC. Both techniques appeared effective in terms of resolution of symptoms, prevention of pathologic fractures, and early facilitation of weight-bearing. PC showed more clinical safety, as no major systemic complications occurred. However, due to the relative paucity of large clinical trials, the decision of augmentation of cementoplasty should be individualized according to the size and location of metastatic lesions and the overall medical condition of patients.